Development of robust multifunctional CrNiCo-P/GCN catalyst for oxygen evolution reaction, electrochemical sensing, and photodegradation of roxarsone. Issue 43 (25th October 2022) - Manavalan, Shaktivel; Veerakumar, Pitchaimani; Chen, Shen-Ming; Karuppusamy, Naveen
Abstract : In this study, we designed a CrNiCo-P/GCN composite for use as a high-performance multifunctional catalyst for the oxygen evolution reaction (OER), electrochemical determination, and photodegradation of roxarsone (ROX). Abstract : In this study, we designed a CrNiCo-P/GCN composite for use as a high-performance multifunctional catalyst for the oxygen evolution reaction (OER), electrochemical determination, and photodegradation of roxarsone (ROX). CrNiCo-P/GCN demonstrates favorable charge resistance and electrical conductance due to its intrinsic properties. It exhibits an admirable OER overpotential of 290 mV with a lower Tafel plot value of 125 mV dec −1 in alkaline media and compared with the control samples. Furthermore, this composite also demonstrates high performance in electrochemical sensing of ROX over a wide concentration range of 1–413 μM with a lower limit of detection (LOD) of 31 nM in phosphate buffer. Moreover, this composite is a promising electrocatalyst for ROX sensors in practical analysis and also possesses excellent photodegradation of ROX under visible light irradiation.